Structural Characteristics of Games and Online Consumer Behaviour: an Analysis in the Italian Gambling Market - Calvosa, Paolo (European Scientific Journal, ESJ, 2022)
The rapid growth of e-commerce over the last years has sparked a stream of research that has analysed the impact of Internet retailing on consumer behavior. This paper intends to offer a contribution, in the field of management studies, to the understanding of the reasons why the level of e-commerce use in a specific service sector, that of gambling, is different for different categories of services offered. In particular, the aims of this work is to analyze how the nature and specific characteristics of the different types of games could influence the customers’ decisions in terms of choice between digital and physical purchase channels. Thus, consequently, impacting the degree of development of online sales for the different types of gambling. This analysis is carried out in the context of one of the main national legal gambling markets in the world, the Italian one, in which Internet gambling is now a mature and consolidated industry. The results of the analysis have shown that for most of the traditional betting categories offered in Italy – Lotteries, Lotto, Totalisator numerical game, Bingo, Virtual bets – the nature and the distinctive characteristics of the game give little emphasis to the potential benefits usually associated with online gambling, and this has determined a reduced development of online sales. Only for Sports-based games (sports betting) the nature and characteristics of the game seem to have exploited a number of significant benefits that Internet gambling offers to players. This helps to understand why betting websites for Sports-based games have become the main channel of purchase in Italy. These results have interesting managerial implications for gambling operators, as discussed in this work.